In Search of a Theology of Reconciliation in the Korean Peninsula. (April 2018) - Kim, Sebastian C. H.
Peace and reconciliation are vital theological concepts: God reconciles himself with us through Christ, and likewise, we are called to become reconciled with one another. But how can this theological understanding be applied to peace and reconciliation between the two Koreas? I discuss here some of the theological efforts that have emerged, drawn from (1) Korean experiences of captivity to ideological differences, (2) distrust and despair, and (3) differing identities between North and South. If Christian theology is to address these issues, we must explore further the meaning of the key concepts Jubilee, han, and shared identity.